Explaining Jamaica's growth puzzle : a comparative growth accounting exercise : draft - Thomas, Damani ([Caribbean Centre of Money & Finance] [St. Augustine]TT, 2007)
Discusses Jamaica's growth performance. Notes that in spite of Jamaica's consistently high investment rate relative to other islands within the Caribbean region, the country continues to record lower growth. Concludes that the political and institutional environment within a country is an important factor in explaining growth within the Caribbean region.